Is medication a risk factor for dental caries among older people? - Thomson WM, Spencer AJ, Slade GD, Chalmers JM (Blackwell Synergy, 2002)
This study examined the association between chronic medication exposure and 5-year dental caries increment among older people, using a theoretical model whereby xerogenic medication is thought to lead to increased caries by either (i) chronically lowering salivary flow, thus reducing salivary buffering of plaque acids, or (ii) producing the symptoms of dry mouth, leading to symptomatic relief through the use of cariogenic drinks and foodstuffs.